2001
DOI: 10.1096/fj.00-0681fje
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of arginase in microvascular endothelial cells counteracts nitric oxide‐mediated vasodilatory function

Abstract: Arginase shares a common substrate, L-arginine, with nitric oxide (NO) synthase (NOS). It is thought that arginase, if it is expressed in the endothelium, might play a pivotal role in the regulation of NO-mediated vasodilation by reducing the L-arginine availability to NOS. In the present study, we wanted to determine whether arginase is expressed and active in coronary arterioles and to demonstrate whether endothelial arginase can influence NO production and play a functional role in regulating NO-mediated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
203
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(225 citation statements)
references
References 36 publications
17
203
1
2
Order By: Relevance
“…Arg I and Arg II expression has also been demonstrated in the penis (11,16) and A293 cells overexpressing NOS1 (44), where reciprocal regulation of Arg and constitutive NOS1 exists. Our published data (10) and those of other researchers (20,45,46) support the notion that Arg isoforms are expressed constitutively in vascular endothelium and may (as in the airway, the penis, and A293 cells) modulate NOS activity by regulating L-arginine availability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Arg I and Arg II expression has also been demonstrated in the penis (11,16) and A293 cells overexpressing NOS1 (44), where reciprocal regulation of Arg and constitutive NOS1 exists. Our published data (10) and those of other researchers (20,45,46) support the notion that Arg isoforms are expressed constitutively in vascular endothelium and may (as in the airway, the penis, and A293 cells) modulate NOS activity by regulating L-arginine availability.…”
Section: Discussionsupporting
confidence: 87%
“…Whereas Arg II is expressed exclusively in the cardiac myocytes, both Arg I and II are found in whole-heart homogenates. These findings most likely reflect the Arg that is present in cell types other than myocytes, such as endothelial cells that have been shown to express Arg I (10,20). Consistent with the data from WB, immunostaining demonstrated Arg II but not Arg I in isolated myocytes (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Previously, Berkowitz et al (6) had shown that both arginase isotypes were expressed in the rat aortic endothelium. Arginase I had been found to be constitutively expressed in endothelial cells (35), whereas arginase II appeared to be inducible in response to cytokines (8). White et al (32) have demonstrated that arginase type I knockdown could enhance NOS activity in adult rat thoracic aortic tissue, and Zhang et al (35) had shown in the porcine coronary artery that arginase type I is responsible for modulating the endothelial-dependent relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Arginase I had been found to be constitutively expressed in endothelial cells (35), whereas arginase II appeared to be inducible in response to cytokines (8). White et al (32) have demonstrated that arginase type I knockdown could enhance NOS activity in adult rat thoracic aortic tissue, and Zhang et al (35) had shown in the porcine coronary artery that arginase type I is responsible for modulating the endothelial-dependent relaxation. Bachetti et al (4) demonstrated that both isoforms were expressed in human umbilical vein endothelial cells (HUVEC) with a predominance of the type I isoform.…”
Section: Discussionmentioning
confidence: 99%